Electrocatalytic Oxidation and Sensitive Determination of Paracetamol Based on Nanosheets Self‐assembled Lindgrenite Microflowers. Issue 5 (7th January 2020) - Fu, Rong; Shen, Mingju; Ding, Yaping; Li, Musen; Li, Li; Ren, Zhongming; Wu, Qingsheng
Abstract: In this work, the nanosheet‐assembled lindgrenite microflowers (chemical formula: Cu3 Mo2 O9 ) were synthesised through a simple process and low‐cost raw materials at room temperature in aqueous solution without using any surface‐active agent. The tightly interlaced nanosheets, like petals, can increase the specific surface area, which can bring about higher electrocatalytic activity and electroanalysis sensitivity. Thus, lindgrenite microflowers were prepared as an electrochemical sensor and successfully applied in the detection of paracetamol through the modified glass carbon electrode. Furthermore, this electrochemical reaction process was simulated at the ab‐initio level to reveal the catalytic mechanism, and the simulation results agreed well with electrochemical experiments. The electrochemical performance of the lindgrenite microflowers modified glassy carbon electrode (GCE) was studied by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The linearity of paracetamol ranged from 0.05 to 1200 μM (IT method) and 0.05 to 1000 μM (DPV method), low detection limit (0.01 μM) and high sensitivity (5.11 mA mM −1 cm −2 ) towards paracetamol. Moreover, this sensor was applied to detect paracetamol in human blood serum samples. The excellent results demonstrated that the prepared electrode not only showed a desirable linear range towards paracetamol but also exhibited practical applicability and reliability towards human serum samples detection. Abstract :